Wound healing gene therapy: cartilage regeneration induced by vascular endothelial growth factor plasmid - Kolostova, Katarina; Taltynov, Oliver; Pinterova, Daniela; Boubelik, Michael; Raska, Otakar; Hozak, Pavel; Jirkovska, Marie; Bobek, Vladimir (American journal of otolaryngology, 2012)
AIMS: The identification of growth factors and cytokines with angiogenic activity has enabled new therapeutic treatments for a variety of diseases; this concept is called therapeutic angiogenesis. The vascular endothelial growth factor (VEGF) is the most critical regulator of vascular formation. In the present study, we were interested in the therapeutic angiogenesis effect using plasmid transfer of human complementary DNA VEGF(165) (phVEGF(165)) in experimental skin and cartilage trauma. METHODS: Ten BALB/c mice were used for cartilage injury model. At 6 weeks of age, all mice were ear-punched, resulting in 2-mm-diameter puncture through the center of both pinnae. Each mouse got phVEGF(165) injection into the first ear and vector without insert or saline injection into the second one. The healing process was followed. The hollow diameter was measured on days 0, 14, and 42. Histological sections of experimental and control pinnae were taken from days 1, 3, 5, 7, 9, 11, 13, 15, 20, and 30 after experimental injury for hematoxylin and eosin and periodic acid Schiff staining and for human VEGF immunocytochemistry. The expression of human VEGF was also checked by real-time polymerase chain reaction in formalin-fixed, paraffin-embedded tissue sections. KEY FINDINGS: In BALB/c mouse strain, a significant angiogenesis promotion and cartilage repair were observed after phVEGF(165) injection into the punched ear area. SIGNIFICANCE: We suggest that administering phVEGF(165) leads to faster cartilage regeneration even if not only on the angiogenic basis.
Keywords: Analysis of Variance; Animals; Feasibility Studies; Regeneration; Cartilage; Wound Healing; vaskulární endoteliální růstový faktor A; Immunohistochemistry; fyziologická neovaskularizace; Mice; Vascular Endothelial Growth Factor A; Mice, Inbred BALB C; myši; imunohistochemie; regenerace; analýza rozptylu; studie proveditelnosti; plazmidy; modely nemocí na zvířatech; myši inbrední BALB C; hojení ran; Disease Models, Animal; chrupavka; Neovascularization, Physiologic; Plasmids; zvířata; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction